Building a Positive School Image: Effective Strategies for Islamic Full-Day Primary Education - Yasin, Muhamad (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The objective of this article is to examine the strategies employed by the school to enhance its reputation and stimulate public interest. The responsibility for determining the most appropriate educational establishment for a child falls upon the prospective parents of students. It is reasonable to posit that quality schools, including those at the elementary level, will be in demand within the community. Furthermore, educational institutions that have a positive reputation and espouse values such as Islamic education, which offers a distinct advantage in terms of general and religious education curricula, are likely to be well-regarded. The implementation of an Islamic full-day school curriculum has been demonstrated to be an effective strategy for fostering a positive image of the school and attracting public interest. It is therefore of interest to examine the success of the primary school work. This research employs a qualitative approach, specifically a case study, and data are collected directly from the natural setting. The findings indicate that the school undertook five initiatives to enhance its image: (1) promotion to increase awareness of the school and its offerings, (2) competitive advantage in service quality, (3) management of facilities and infrastructure, (4) management of teachers, and (5) curriculum development. These efforts have been effective in generating public interest in the school.